(untitled) (Research, Society and Development, 2020)
Knowledge and quality have become essential in organizations to obtain competitive advantages, these tools make human capital relevant, enabling process improvements and increased customer satisfaction, whether internal or external, and making the organization profitable. In this article, the case study methodology was applied, together with the proposal to disseminate knowledge and innovation to reduce non-conformities within the organization, by surveying the causes, monitoring the indicators and verifying the influence of the use of concepts. knowledge and quality management tools in the organization’s production processes. Significant results were obtained after the implementation of knowledge management and quality management within the organization, customer loyalty and reduction of nonconformities. This efficiency and effectiveness assist in management and improvement the organization’s performance.